Hoarseness as A Window into the Complexity of Supraglottic Carcinoma: A Case Report and Literature Review - Kholifah Yulia Astuti; Siti Nurhikmah (Universitas Malahayati Lampung, 2023)
ABSTRACT Laryngeal carcinoma ranks among the most prevalent malignancies affecting the head and neck, with supraglottic carcinoma emerging as the predominant subtype, particularly in certain developing regions characterized by prevalent risk factors such as alcohol consumption and smoking. Hoarseness, characterized by a change in the voice, constitutes approximately 1% of all primary care consultations. The predominant etiologies include acute and chronic laryngitis, responsible for 42.1% and 9.7% of cases, respectively, followed by functional dysphonia, benign and malignant tumors, neurogenic factors, and the natural aging process. A 65-year-old male, with a history of active smoking, was referred from a primary healthcare center due to complaints of throat pain and worsening hoarseness that had persisted for one year. The significant airway obstruction observed in this patient underscores the importance of discussing available management options in such cases. It is crucial for primary care physicians to recognize the clinical signs presented by the patient promptly in order to initiate the appropriate management without delay. Regrettably, tend to seek medical attention at an advanced stage of the disease, resulting in a notably unfavorable overall survival rate. Keyword: Laryngeal Carcinoma, Supraglottic Carcinoma, Hoarseness, Survival Rate